Upaya Peningkatan Kompetensi Pegawai Dan Pemenuhan Formasi Kebutuhan Pegawai Pada Dinas Lingkungan Hidup Kabupaten Malang - Ila Nur Janah; Ismi Iftikad (Pakis Journal Institute, 2024)
This service aims to understand the efforts carried out by the Malang Regency Environmental Service (DLH) to develop worker productivity. This regulation seeks to ascertain and organize the abilities of staff who work at DLH so that they fulfill the specified qualifications and make an ideal contribution to an organization. The way to develop employee abilities is through education and training. However, implementation is still hampered by the unmet number of employees which results in an increase in workload. The service that has been carried out, obtained information that the composition of the workforce needs at DLH in the Malang Regency area, the addition of workers is due to the presence of retirees. Therefore, DLH in the Malang Regency area should carry out monitoring of the addition of workload to employee needs until there is regularity between workload and number of employees.